(untitled) (Моделювання, керування та інформаційні технології, 2025)
We use the method of a priori inequalities in negative norms to prove the well-posedness of the Dirichlet initial boundary value problem for the differential and integro-differential equations of the pseudo-parabolic type with integral terms of the Volterra type. Further we provide theorem on optimal control existence. The result is obtained under less assumptions on the equation’s coefficients than in similar papers. Методом апріорних нерівностей у від’ємних нормах доведено коректність початково-крайової задачі Діріхле для диференціальних та інтегро-диференціальних рівнянь псевдопараболічного типу з інтегральними членами типу Вольтерра. Наведено теорему про існування точкового оптимального керування. Результат отримано за менших припущень щодо коефіцієнтів рівняння, у порівнянні з аналогічними роботами.